Perancangan Logo Komunitas “Tanda Mata Kreatif” sebagai Upaya Meningkatkan Brand Awareness - Debio Pararta Wiguna; Aris Kurnia Wicaksono; Eka Wahyu Primadani; Rahmania Almira (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2024)
In a community, there is something that is important and has a function as a comparison between one community and another, namely the presence of a logo. The founding of the Tanda Mata Kreatif community began with the desire of Ari Nanda Suria as Chair of Tanda Mata Kreatif to develop potential and interest in filmmaking and enrich culture through audio-visual media so that Tanda Mata Kreatif becomes a forum for students who have an interest in the world of film. However, the Tanda Mata Kreatif community does not have a permanent logo identity so this community is difficult to recognize for students or students to join. Therefore, it is necessary to study the literature to design the right logo for the Tanda Mata Kreatif Sign community and apply qualitative methods to analyze branding in the Tanda Mata Kreatif Sign community. This research explains the logo design process for the Tanda Mata Kreatif Sign community. The research approach used is a qualitative approach with interview and observation collection techniques. Analysis was carried out in three stages: data collection, reduction, and presentation. The results of the research are logos, visual identities, and supporting media for the Tanda Mata Kreatif community.